Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 59518 by Mr X pcx last updated on 11/May/19

if  x+y+z=1  x^2  +y^2  +z^2 =2  x^3  +y^3  +z^3 =3  calculste  x^5 +y^5  +z^5

$${if}\:\:{x}+{y}+{z}=\mathrm{1} \\ $$$${x}^{\mathrm{2}} \:+{y}^{\mathrm{2}} \:+{z}^{\mathrm{2}} =\mathrm{2} \\ $$$${x}^{\mathrm{3}} \:+{y}^{\mathrm{3}} \:+{z}^{\mathrm{3}} =\mathrm{3}\:\:{calculste} \\ $$$${x}^{\mathrm{5}} +{y}^{\mathrm{5}} \:+{z}^{\mathrm{5}} \\ $$

Commented by MJS last updated on 11/May/19

we had this several times before. the answer is 6

$$\mathrm{we}\:\mathrm{had}\:\mathrm{this}\:\mathrm{several}\:\mathrm{times}\:\mathrm{before}.\:\mathrm{the}\:\mathrm{answer}\:\mathrm{is}\:\mathrm{6} \\ $$

Answered by MJS last updated on 11/May/19

put x=a; y=b−ci; z=b+ci  x+y+z=1 ⇒ a+2b=1 ⇒ a=1−2b  x^2 +y^2 +z^2 =2 ⇒ a^2 +2b^2 −2c^2 =2 ⇒       ⇒ 6b^2 −4b−2c^2 +1=2 ⇒ c=((√(2(6b^2 −4b−1)))/2)  x^3 +y^3 +z^3 =3 ⇒ a^3 +2b(b^2 −3c^2 )=3 ⇒       ⇒ −24b^3 +24b^2 −3b+1=3 ⇒       ⇒ b^3 −b^2 +(1/8)b+(1/(12))=0    x^5 +y^5 +z^5 =a^5 +2b(b^4 −10b^2 c^2 +5c^4 )=       =−60b^3 +60b^2 −((15)/2)b+1=−60(b^3 −b^2 +(1/8)b−(1/(60)))    b^3 −b^2 +(1/8)b+(1/(12))=0 ⇒ b^3 −b^2 +(1/8)b−(1/(60))=−(1/(10)) ⇒       ⇒ −60(b^3 −b^2 +(1/8)b−(1/(60)))=6 ⇒       ⇒ x^5 +y^5 +z^5 =6

$$\mathrm{put}\:{x}={a};\:{y}={b}−{c}\mathrm{i};\:{z}={b}+{c}\mathrm{i} \\ $$$${x}+{y}+{z}=\mathrm{1}\:\Rightarrow\:{a}+\mathrm{2}{b}=\mathrm{1}\:\Rightarrow\:{a}=\mathrm{1}−\mathrm{2}{b} \\ $$$${x}^{\mathrm{2}} +{y}^{\mathrm{2}} +{z}^{\mathrm{2}} =\mathrm{2}\:\Rightarrow\:{a}^{\mathrm{2}} +\mathrm{2}{b}^{\mathrm{2}} −\mathrm{2}{c}^{\mathrm{2}} =\mathrm{2}\:\Rightarrow \\ $$$$\:\:\:\:\:\Rightarrow\:\mathrm{6}{b}^{\mathrm{2}} −\mathrm{4}{b}−\mathrm{2}{c}^{\mathrm{2}} +\mathrm{1}=\mathrm{2}\:\Rightarrow\:{c}=\frac{\sqrt{\mathrm{2}\left(\mathrm{6}{b}^{\mathrm{2}} −\mathrm{4}{b}−\mathrm{1}\right)}}{\mathrm{2}} \\ $$$${x}^{\mathrm{3}} +{y}^{\mathrm{3}} +{z}^{\mathrm{3}} =\mathrm{3}\:\Rightarrow\:{a}^{\mathrm{3}} +\mathrm{2}{b}\left({b}^{\mathrm{2}} −\mathrm{3}{c}^{\mathrm{2}} \right)=\mathrm{3}\:\Rightarrow \\ $$$$\:\:\:\:\:\Rightarrow\:−\mathrm{24}{b}^{\mathrm{3}} +\mathrm{24}{b}^{\mathrm{2}} −\mathrm{3}{b}+\mathrm{1}=\mathrm{3}\:\Rightarrow \\ $$$$\:\:\:\:\:\Rightarrow\:{b}^{\mathrm{3}} −{b}^{\mathrm{2}} +\frac{\mathrm{1}}{\mathrm{8}}{b}+\frac{\mathrm{1}}{\mathrm{12}}=\mathrm{0} \\ $$$$ \\ $$$${x}^{\mathrm{5}} +{y}^{\mathrm{5}} +{z}^{\mathrm{5}} ={a}^{\mathrm{5}} +\mathrm{2}{b}\left({b}^{\mathrm{4}} −\mathrm{10}{b}^{\mathrm{2}} {c}^{\mathrm{2}} +\mathrm{5}{c}^{\mathrm{4}} \right)= \\ $$$$\:\:\:\:\:=−\mathrm{60}{b}^{\mathrm{3}} +\mathrm{60}{b}^{\mathrm{2}} −\frac{\mathrm{15}}{\mathrm{2}}{b}+\mathrm{1}=−\mathrm{60}\left({b}^{\mathrm{3}} −{b}^{\mathrm{2}} +\frac{\mathrm{1}}{\mathrm{8}}{b}−\frac{\mathrm{1}}{\mathrm{60}}\right) \\ $$$$ \\ $$$${b}^{\mathrm{3}} −{b}^{\mathrm{2}} +\frac{\mathrm{1}}{\mathrm{8}}{b}+\frac{\mathrm{1}}{\mathrm{12}}=\mathrm{0}\:\Rightarrow\:{b}^{\mathrm{3}} −{b}^{\mathrm{2}} +\frac{\mathrm{1}}{\mathrm{8}}{b}−\frac{\mathrm{1}}{\mathrm{60}}=−\frac{\mathrm{1}}{\mathrm{10}}\:\Rightarrow \\ $$$$\:\:\:\:\:\Rightarrow\:−\mathrm{60}\left({b}^{\mathrm{3}} −{b}^{\mathrm{2}} +\frac{\mathrm{1}}{\mathrm{8}}{b}−\frac{\mathrm{1}}{\mathrm{60}}\right)=\mathrm{6}\:\Rightarrow \\ $$$$\:\:\:\:\:\Rightarrow\:{x}^{\mathrm{5}} +{y}^{\mathrm{5}} +{z}^{\mathrm{5}} =\mathrm{6} \\ $$

Commented by MJS last updated on 11/May/19

x+y+z=α  x^2 +y^2 +z^2 =β  x^3 +y^3 +z^3 =γ  ⇒  x^4 +y^4 +z^4 =(1/6)α^4 −α^2 β+(4/3)αγ+(1/2)β^2   x^5 +y^5 +z^5 =(1/6)α^5 −(5/6)α^3 β+(5/6)α^2 γ+(5/6)βγ

$${x}+{y}+{z}=\alpha \\ $$$${x}^{\mathrm{2}} +{y}^{\mathrm{2}} +{z}^{\mathrm{2}} =\beta \\ $$$${x}^{\mathrm{3}} +{y}^{\mathrm{3}} +{z}^{\mathrm{3}} =\gamma \\ $$$$\Rightarrow \\ $$$${x}^{\mathrm{4}} +{y}^{\mathrm{4}} +{z}^{\mathrm{4}} =\frac{\mathrm{1}}{\mathrm{6}}\alpha^{\mathrm{4}} −\alpha^{\mathrm{2}} \beta+\frac{\mathrm{4}}{\mathrm{3}}\alpha\gamma+\frac{\mathrm{1}}{\mathrm{2}}\beta^{\mathrm{2}} \\ $$$${x}^{\mathrm{5}} +{y}^{\mathrm{5}} +{z}^{\mathrm{5}} =\frac{\mathrm{1}}{\mathrm{6}}\alpha^{\mathrm{5}} −\frac{\mathrm{5}}{\mathrm{6}}\alpha^{\mathrm{3}} \beta+\frac{\mathrm{5}}{\mathrm{6}}\alpha^{\mathrm{2}} \gamma+\frac{\mathrm{5}}{\mathrm{6}}\beta\gamma \\ $$

Commented by maxmathsup by imad last updated on 11/May/19

thanks sir mjs

$${thanks}\:{sir}\:{mjs} \\ $$

Commented by Tawa1 last updated on 21/Jul/19

Sir reference to the identity.  I did not get 6 when i substitute  α = 1, β = 2, γ = 3    for   α^5  + β^5  + γ^5   and i got  ((25)/6)  for    α^4  + β^4  + γ^4

$$\mathrm{Sir}\:\mathrm{reference}\:\mathrm{to}\:\mathrm{the}\:\mathrm{identity}. \\ $$$$\mathrm{I}\:\mathrm{did}\:\mathrm{not}\:\mathrm{get}\:\mathrm{6}\:\mathrm{when}\:\mathrm{i}\:\mathrm{substitute}\:\:\alpha\:=\:\mathrm{1},\:\beta\:=\:\mathrm{2},\:\gamma\:=\:\mathrm{3}\:\:\:\:\mathrm{for}\:\:\:\alpha^{\mathrm{5}} \:+\:\beta^{\mathrm{5}} \:+\:\gamma^{\mathrm{5}} \\ $$$$\mathrm{and}\:\mathrm{i}\:\mathrm{got}\:\:\frac{\mathrm{25}}{\mathrm{6}}\:\:\mathrm{for}\:\:\:\:\alpha^{\mathrm{4}} \:+\:\beta^{\mathrm{4}} \:+\:\gamma^{\mathrm{4}} \\ $$

Commented by MJS last updated on 21/Jul/19

((25)/6) is the right answer  I′ll look into it again

$$\frac{\mathrm{25}}{\mathrm{6}}\:\mathrm{is}\:\mathrm{the}\:\mathrm{right}\:\mathrm{answer} \\ $$$$\mathrm{I}'\mathrm{ll}\:\mathrm{look}\:\mathrm{into}\:\mathrm{it}\:\mathrm{again} \\ $$

Commented by Tawa1 last updated on 21/Jul/19

Okay sir,  God bless you sir.      That means the identity is correct for   α^4  + β^4  + γ^4  = ((25)/4)

$$\mathrm{Okay}\:\mathrm{sir},\:\:\mathrm{God}\:\mathrm{bless}\:\mathrm{you}\:\mathrm{sir}. \\ $$$$\:\:\:\:\mathrm{That}\:\mathrm{means}\:\mathrm{the}\:\mathrm{identity}\:\mathrm{is}\:\mathrm{correct}\:\mathrm{for}\:\:\:\alpha^{\mathrm{4}} \:+\:\beta^{\mathrm{4}} \:+\:\gamma^{\mathrm{4}} \:=\:\frac{\mathrm{25}}{\mathrm{4}} \\ $$

Commented by MJS last updated on 21/Jul/19

yes

$$\mathrm{yes} \\ $$

Commented by MJS last updated on 21/Jul/19

(1/6)×1^5 −(5/6)×1^3 ×2+(5/6)×1^2 ×3+(5/6)×2×3=  =(1/6)−((10)/6)+((15)/6)+((30)/6)=((36)/6)=6  you′ll have to check your calculation for typos

$$\frac{\mathrm{1}}{\mathrm{6}}×\mathrm{1}^{\mathrm{5}} −\frac{\mathrm{5}}{\mathrm{6}}×\mathrm{1}^{\mathrm{3}} ×\mathrm{2}+\frac{\mathrm{5}}{\mathrm{6}}×\mathrm{1}^{\mathrm{2}} ×\mathrm{3}+\frac{\mathrm{5}}{\mathrm{6}}×\mathrm{2}×\mathrm{3}= \\ $$$$=\frac{\mathrm{1}}{\mathrm{6}}−\frac{\mathrm{10}}{\mathrm{6}}+\frac{\mathrm{15}}{\mathrm{6}}+\frac{\mathrm{30}}{\mathrm{6}}=\frac{\mathrm{36}}{\mathrm{6}}=\mathrm{6} \\ $$$$\mathrm{you}'\mathrm{ll}\:\mathrm{have}\:\mathrm{to}\:\mathrm{check}\:\mathrm{your}\:\mathrm{calculation}\:\mathrm{for}\:\mathrm{typos} \\ $$

Commented by Tawa1 last updated on 21/Jul/19

Wow great sir. God bless you sir.

$$\mathrm{Wow}\:\mathrm{great}\:\mathrm{sir}.\:\mathrm{God}\:\mathrm{bless}\:\mathrm{you}\:\mathrm{sir}. \\ $$

Commented by Tawa1 last updated on 21/Jul/19

One more thing sir. How do you get the identity sir.  when you are less busy

$$\mathrm{One}\:\mathrm{more}\:\mathrm{thing}\:\mathrm{sir}.\:\mathrm{How}\:\mathrm{do}\:\mathrm{you}\:\mathrm{get}\:\mathrm{the}\:\mathrm{identity}\:\mathrm{sir}. \\ $$$$\mathrm{when}\:\mathrm{you}\:\mathrm{are}\:\mathrm{less}\:\mathrm{busy} \\ $$

Commented by MJS last updated on 21/Jul/19

I′ll repost this as a new question plus answer  plus explanation

$$\mathrm{I}'\mathrm{ll}\:\mathrm{repost}\:\mathrm{this}\:\mathrm{as}\:\mathrm{a}\:\mathrm{new}\:\mathrm{question}\:\mathrm{plus}\:\mathrm{answer} \\ $$$$\mathrm{plus}\:\mathrm{explanation} \\ $$

Commented by Tawa1 last updated on 21/Jul/19

Wow great. I will learn from it

$$\mathrm{Wow}\:\mathrm{great}.\:\mathrm{I}\:\mathrm{will}\:\mathrm{learn}\:\mathrm{from}\:\mathrm{it} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com